Equipping Young Entrepreneurs: How Smart Presentation Apps Foster Vocational High-School Students’ Innovation - Ni Luh Putu Ning Septyarini Putri Astawa; Ida Ayu Oka Purnami (International Journal of Community Service Learning, 2024)
Smart presentation apps are software or digital platforms designed to help users create engaging and effective presentations. They are often equipped with features such as a wide selection of slide designs, visual elements, templates, animation effects, and the ability to easily insert images, videos, graphics, and text. This research aims to improve young entrepreneurs' and vocational high school students' presentation skills in presenting products or businesses in the ideation stage. This activity involved 80 participants and consisted of several stages: team division, needs analysis, solution determination, preparation, implementation, and evaluation. Explicit methods were used to provide instructions during implementation. The pre-test and post-test comparison results showed a significant change in the participants' abilities before and after the activity was carried out. This study concludes that using the Canva application significantly increases creativity when creating innovative presentations. This study implies that Canva helps students' independent practice by allowing participants to explore their creativity and ideas when making presentations to showcase their products.